Characterization of the Role of Integrin α5β1 in Platelet Function, Hemostasis, and Experimental Thrombosis - Janus-Bell, Emily; Yakusheva, Alexandra; Scandola, Cyril; Receveur, Nicolas; Ahmed, Usman Muhammad; Mouriaux, Clarisse; Bourdon, Catherine; Loubière, Cécile; Eckly, Anita; Senis, Yotis A.; Panteleev, Mikhail A.; Gachet, Christian; Mangin, Pierre H. (Thrombosis and Haemostasis, 2021)
Objective Integrins are key regulators of various platelet functions. The pathophysiological importance of most platelet integrins has been investigated, with the exception of α5β1, a receptor for fibronectin. The aim of this study was to characterize the role of α5β1 in megakaryopoiesis, platelet function, and to determine its importance in hemostasis and arterial thrombosis.Approach and Results We generated a mouse strain deficient for integrin α5β1 on megakaryocytes and platelets (PF4Cre-α5−/−). PF4Cre-α5−/− mice were viable, fertile, and presented no apparent signs of abnormality. Megakaryopoiesis appears unaltered as evidence by a normal megakaryocyte morphology and development, which is in agreement with a normal platelet count. Expression of the main platelet receptors and the response of PF4Cre-α5−/− platelets to a series of agonists were all completely normal. Adhesion and aggregation of PF4Cre-α5−/− platelets under shear flow on fibrinogen, laminin, or von Willebrand factor were unimpaired. In contrast, PF4Cre-α5−/− platelets displayed a marked decrease in adhesion, activation, and aggregation on fibrillar cellular fibronectin and collagen. PF4Cre-α5−/− mice presented no defect in a tail-bleeding time assay and no increase in inflammatory bleeding in a reverse passive Arthus model and a lipopolysaccharide pulmonary inflammation model. Finally, no defects were observed in three distinct experimental models of arterial thrombosis based on ferric chloride-induced injury of the carotid artery, mechanical injury of the abdominal aorta, or laser-induced injury of mesenteric vessels.Conclusion In summary, this study shows that platelet integrin α5β1 is a key receptor for fibrillar cellular fibronectin but is dispensable in hemostasis and arterial thrombosis.
Keywords: platelets; arterial thrombosis; integrin α5β1; fibronectin